Chewing difficulties, oral health, and nutritional status in adults with intellectual disabilities: A cross‐sectional study - YILDIRIM, HATİCE SELİN (My University, 2024)
Background: Chewing difficulty, poor oral health, inadequate and imbalanced nutrition are serious health problems in individuals with intellectual disabilities. The participants' chewing abilities, oral health and nutritional status were analysed in this study. Methods: Forty-five adult participants with intellectual disabilities were included. Anthropometric measurements, oral health assessments, chewing ability evaluations and dietary intake analyses were conducted. Results: A 56.8% of the participants were classified as overweight or obese. Teeth grinding was reported in 33.3% of the participants, while 40.0% experienced drooling. All participants with Down syndrome and 58.6% of the participants with developmental delay had chewing difficulties. Inadequate nutrient intake was observed and the fibre, vitamins B1, B3, B9, sodium, phosphorus and iron intakes were significantly lower than reference values in those with chewing difficulty (p < .05). Conclusions: Chewing difficulties were associated with lower intake of certain nutrients, highlighting the importance of addressing oral health and dietary counselling in this population.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)